Synthesis, characterization, fluorescence spectra and energy transfer properties of a novel unsymmetrical zinc phthalocyanine with peripherally coordinated Ru(II) complex - Ceylan, Nurufe; Gumrukcu, Gulsah; Karaoglan, Gulnur Keser; Gul, Ahmet (ELSEVIER SCIENCE SA, 2015)
A novel unsymmetrically substituted zinc (II) phthalocyanine was synthesized through a multistep reaction sequence starting first with cyclotetramerization of 4-(4-nitrophenoxy) phthalonitrile and 4-(hexylthio) phthalonitrile, then reduction of nitro group to amino functionality and then its condensation with 1,10-phenanthroline-4-carbaldehyde. Finally, a new multicomponent ZnPc-Ru(bpy)(2)(phen) system consisting of a zinc-phthalocyanine core linked through a nonconjugated bridge to ruthenium(II) bis (bipyridine) complex was synthesized using the reaction of the phthalocyanine bearing a 4-substituted-1,10-phenanthroline subunit and [Ru(bpy)(2)Cl-2]center dot 2H(2)O. The new compounds have been characterized by elemental analysis, IR, H-1-NMR, UV-vis and MALDI-TOF MS spectral data. Intramolecular electronic interactions in these dyads were studied by absorption, and emission spectroscopy. Upon photoexcitation, these dyads exhibit intramolecular energy transfer from the Ru(II) chromophore to the ZnPc moiety. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Ruthenium bis(pyridyl) complex; Phenanthroline; Unsymmetrical phthalocyanines; Multicomponent system; PHOTOPHYSICAL PROPERTIES; OPTICAL-PROPERTIES; THIN-FILMS; SUBSTITUTED PHTHALOCYANINES; PHOTOINDUCED PROCESSES; II PHTHALOCYANINE; PORPHYRIN; ELECTROCHEMISTRY; DERIVATIVES; VAPORS; Materials Science; Physics; Polymer Science